Genome-Wide Association of Genetic Variants With Refraction, Axial Length, and Corneal Curvature: A Longitudinal Study of Chinese Schoolchildren - Lin, Yaoyao; Ding, Yu; Jiang, Dandan; Li, Chunchun; Huang, Xiaoqiong; Liu, Linjie; Xiao, Haishao; Vasudevan, Balamurali; Chen, Yanyan (Frontiers in Genetics, 2020)
Background: Myopia is a common eye disorder that is approaching epidemic proportions worldwide. A genome-wide association study identified AREG (rs12511037), GABRR1 (rs13215566) and PDE10A (rs12206610) as being associated with refractive error in Asian populations. The present study investigated the associations between these three genetic variants and the occurrence and development of myopia, spherical equivalent refraction (SER), axial length (AL), and corneal curvature (CC) in a cohort of southeastern Chinese schoolchildren. Methods: We examined and followed 550 children in grade 1 enrolled in the Wenzhou Epidemiology of Refractive Error (WERE) project. During the 4-year follow-up, noncycloplegic refraction was evaluated twice each year, and the AL and CC were measured once every year. Age, sex, and the amounts of time spent on near work and outdoors were documented with a questionnaire. Sanger DNA sequencing was used to genotype single nucleotide polymorphisms (SNPs). SNPtest software was used to identify potential genetic variants associated with myopia, SER, AL and CC. Ten thousand permutations were used to correct for multiple testing. Results: In total, 469 children, including 249 (53.1%) boys and 220 (46.9%) girls, were included in analyses. The mean age of all the children was 6.33±0.48 years. After adjusting for age, sex, time spent on near work and time spent outdoors, neither the genotypes nor the allele frequencies of the three SNPs were significantly associated with myopic shift, incident myopia or the change in SER. After adjusting for age, sex, near-work time and outdoor time with 10,000 permutations, the genotype AREG (rs12511037) was associated with an increase in AL (P’ values for the dominant, recessive, additive and general models were 0.0032, 0.0275, 0.0045 and 0.0099, respectively); the genotype PDE10A (rs12206610) was associated with a change in CC in the additive (P’=0.0096), dominant (P’=0.0096) and heterozygous models (P’=0.0096). Conclusion: These findings preliminarily indicate that AREG SNP rs12511037 and PDE10A SNP rs12206610 are etiologically relevant for ocular traits, providing a basis for further exploration of the development of myopia and its molecular mechanism. However, elucidating the role of AREG and PDE10A in the pathogenesis of myopia requires further animal model and human genetic epidemiology studies.